The Improvement of Critical Thinking Skills of Primary School Students Through Guided Inquiry Learning Models with Integrated Peer Instructions - Mohammad Alim Ahaddin; Budi Jatmiko; Zainul Arifin Imam Supardi (Studies in Learning and Teaching, 2020)
This research aims to describe the improvement of critical thinking skills of primary school students in the learning model of teaching Inquiry integrated peer instruction. A research sample is a Grade 5 primary school student with a total of 40 students. Research methods use experimental research with one group pre-test and post-test design. Data collection techniques using tests. The data analysis technique uses statistic inferential. Based on the results of the calculations using N-Gain, it is gained that there is an increase in the critical thinking skills of primary school students, i.e. 12 students gained a high upgrade category and 28 students gained a moderate upgrade category. In addition, it is obtained that students experience the guidance of learning both individually and in class. The result of guided Inquiry model integrated peer instruction provided effect so that there has been an improvement of critical thinking in primary school students. Further research is expected that all students can obtain high increases.